Composição florística e estrutura da comunidade vegetal em diferentes fitofisionomias do Pantanal de Poconé, Mato Grosso - Morais, Rodrigo Ferreira De [UNESP]; Silva, Edna Cavalcante Saraiva Da; Metelo, Mariana Regina Lema; Morais, Fernando Ferreira De [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2013)
The aim of this research was to analyze the composition and structure of the plant community in four phytophysiognomies at Pantanal Poconé-Mato Grosso, assuming that each sample group is a type of community, and there would be a corresponding group of species that characterize that community. We set up five plots of 50 × 50 m and subdivided each one into subplots of 10 × 10 m. In each subplot, individuals with CAP (circunference at breast height) > 10 cm were sampled. To check the structural and floristic similarity of the five vegetation types the unweighted averages grouping method was used - UPGMA, with Jaccard's coefficient and Bray-Curtis, respectively. DCA ordination of plots was used for inundation gradient analysis and TWINSPAN indicator species groups for the three strata. In the four areas 55 species belonging to 30 families were sampled. The UPMGA indicated floristic and structural differences between cambarazal, savanna types and campo de murundu and similarity between the semideciduous formations. The DCA separated the vegetation types according to the level of flooding and TWINSPAN indicated the existence of typical species for each vegetation type. In the Pantanal, some species may be restricted to certain types of vegetation, and these species can be used as indicators of the effect of flooding and possible changes in flood pulse dynamics in plant communities.

Esta pesquisa teve como objetivo analisar a composição e estrutura de comunidade vegetal de quatro fitofisionomias no Pantanal de Poconé, estado de Mato Grosso, partindo do pressuposto de que cada grupo de amostras constitui um tipo de comunidade e haverá um grupo correspondente de espécies que caracterizam a comunidade em particular. Foram implantadas cinco parcelas de 50 × 50 m e subdivididas em subparcelas de 10 ×10 m. Foram considerados na amostragem os indivíduos com CAP (circunferência a altura do peito) > 10 cm. A similaridade florística e estrutural entre as quatro fitofisionomias foram avaliadas pelo método de agrupamento por médias não ponderadas - UPGMA, com uso do coeficiente de Jaccard e Bray-Curtis. Foi utilizada a DCA para ordenação das parcelas e TWINSPAN para análise de espécies indicadoras para as fitofisionomias. Nas quatro fitofisionomias foram amostradas 55 espécies pertencentes a 30 famílias. A UPMGA indicou diferenças florística e estrutural entre cambarazal, floresta semidecidual e cerrado sensu stricto e campo de murundu e similaridade entre as formações semideciduais. A DCA ordenou as fitofisionomias de acordo com o gradiente de inundação e a TWINSPAN indicou a existência de espécies indicadoras para as fitofisionomia.
Floristic composition and structure of the plant community of different phytophysiognomies in the Pantanal of Poconé, Mato Grosso
Keywords: pulso de inundação; espécies indicadoras; flood pulse; indicator species